The impact of rural revitalization talent cultivation on farm household part-time farming: Evidence from the “One Village, One University Student” program - Jiawei Wang; Xia Kuang; Zhipeng Wang; Wenmei Liao; Hailan Qiu (PLoS ONE, 2025)
The key to rural revitalization lies in talent revitalization. Cultivating a workforce that understands agriculture, loves rural areas, and cares for farmers, while retaining talent in rural regions, is of greater significance for comprehensively advancing rural revitalization. From the perspective of farm household part-time farming, this study takes the One Village, One University Student program as an example. Using survey data from 2552 farm households across 12 counties (cities and districts) in Jiangxi Province, China, and employing the ESR model, this study empirically analyzes the impact of rural revitalization talent cultivation on farm household part-time farming. It further explores the differentiated effects of various educational levels and learning modes of talent cultivation on the part-time farming. The results show that rural revitalization talent cultivation significantly reduces the degree of part-time farming, with higher-level education and correspondence education having particularly pronounced effects in enhancing agricultural skills and production efficiency. Based on these findings, this paper proposes policy recommendations to intensify rural revitalization talent cultivation, improve the educational levels and content, optimize educational modes, and strengthen the policy advocacy, aiming to further promote rural economic development and increase farmers’ income.